The burden of multiple sclerosis in Japan. (2nd December 2017) - Nohara, Chiyoko; Hase, Masakazu; Liebert, Ryan; Wu, Ning
Abstract: Aims: Multiple sclerosis (MS) is a disabling autoimmune disease affecting the central nervous system. Few studies have examined the effect of MS on patient outcomes in Japan. The study aim was to quantify MS burden in Japan by comparing MS respondents to matched controls on patient outcomes. Materials and methods: Data from seven administrations of the nationally representative Japan National Health and Wellness Survey (2009–2014 and 2016) were used ( n  = 181, 423). Respondents self-reporting MS diagnosis were compared with respondents not reporting MS. Matched controls were selected using propensity scores. Respondents with MS and matched controls were compared on health-related quality-of-life (HRQoL), work productivity and activity impairment, healthcare resource utilization, and costs. Comparisons were made using Chi-square tests or one-way ANOVAs. Results: A total of 96 respondents with MS and 480 matched controls were included in the analyses. MS respondents reported worse mental (44.35 vs 47.51, p  < .05), physical (33.11 vs 49.04, p  < .001), and role (37.78 vs 47.11, p  < .001) component summary scores (minimally important difference is 3.0). Additionally, MS respondents reported decrements on every health profile sub-scale ( p  < .001) and 5-Level EuroQoL-5 Dimensions outcome ( p  < .01). MS respondents also reported more healthcare provider visits (13.78 vs 6.13) and hospitalizations (3.02 vs 0.70; both, p  < .001), leading to higher direct costs. For work productivity and activity impairment, MS respondents reported more absenteeism (17.50% vs 5.57%), presenteeism (38.11% vs 21.62%), overall work impairment (46.68% vs 25.27%), and activity impairment (46.88% vs 24.90%, all, p  < .001), leading to higher indirect costs. Limitations: Japan NHWS data are cross-sectional, and causal relationships cannot be established. Due to the self-reported nature of the data, responses could not be independently verified. Conclusions: Results suggest MS in Japan is associated with poorer HRQoL and greater work and activity impairment, healthcare resource use, and costs. Improved MS management could benefit both patients and society.